2013
DOI: 10.1016/j.jegh.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Providing detailed information about latent tuberculosis and compliance with the PPD test among healthcare workers in Israel: A randomized controlled study

Abstract: Compliance for latent TB screening is low among HCWs in northeastern Israel. Providing detailed information about latent TB was not associated with increased test compliance. Understanding existing disparities in screening rates and potential barriers to latent TB screening among HCWs is important in order to move forward and successfully increase screening rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The TST is performed by injecting PPD into an individual's forearm and observing the skin induration reaction after 48 h or 72 h from the injection. Although the TST has been the standard for the identification of MTB infection for the past century, it cannot effectively distinguish between MTB infection and either nontuberculous mycobacteria (NTM) infection or Bacillus Calmette-Guérin (BCG) vaccination due to the presence of homologous antigens in PPD [11,12]. Therefore, the TST suffers from high false positive rate and low specificity [13], and these limitations have led to the development of more effective immunodiagnostic tools to identify LTBI.…”
Section: Introductionmentioning
confidence: 99%
“…The TST is performed by injecting PPD into an individual's forearm and observing the skin induration reaction after 48 h or 72 h from the injection. Although the TST has been the standard for the identification of MTB infection for the past century, it cannot effectively distinguish between MTB infection and either nontuberculous mycobacteria (NTM) infection or Bacillus Calmette-Guérin (BCG) vaccination due to the presence of homologous antigens in PPD [11,12]. Therefore, the TST suffers from high false positive rate and low specificity [13], and these limitations have led to the development of more effective immunodiagnostic tools to identify LTBI.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of progression of LTBI, defined as the presence of mycobacterium TB bacteria without the manifestation of signs or symptoms, to TB disease is highest during the first years after infection [4] . Several studies have shown that HCWs are not compliant with screening and/or preventive measures [7,8,9] . Such data have led to a growing interest in improving the detection and proper management of TB infection among HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…11e13 Current diagnostic tests for tuberculosis, which are based on tuberculin, have poor specificity because BCG vaccination and exposure to nontuberculosis mycobacterium produce a similar response as infection with genuine M. tb. 14,15 The PCR assay has a sensitivity and specificity for the TB of sputum and extrapulmonary tuberculosis. 16e18 However, this technology needs expensive reagents and instruments and does not distinguish between living and dead bacteria for clinical judgment.…”
Section: Introductionmentioning
confidence: 99%